Skin-to-skin contact and deaths in newborns weighing up to 1800 grams: a cohort study - Goudard,Marivanda J.F. (2022)
Abstract Objective: To evaluate the association between dose of skin-to-skin contact (SSC) per day and initiation time with the occurrence of deaths in newborns with weight up to 1800g. Method: Multicentric cohort in five Brazilian neonatal units, including newborns with a birth weight of ≤1800g. The time of SSC was registered in individual file, by the team or family during the hospitalization. Maternal and newborn data were obtained through questionnaires applied to mothers and in medical records. Classification Tree was used for data analysis. Results: The performance of the first SSC after 206h was significantly associated with death (p = 0.02). Although there was no association between SSC/day and death (p = 0.09), the number of deaths among those who performed more than 146.9 minutes/day was lower (3;1.5%) than among those who performed this practice for a shorter time (13;6.4%), a fact considered of great clinical importance. Early and late infections present statistically significant associations with the outcome. The chance of death was equal to zero when there was no early infection in the group with the longest duration of SSC. This probability was also equal to zero in the absence of late sepsis for the group with less than 146.9 minutes/day of SSC. Conclusions: The first SSC before 206 hours of life is recommended in order to observe a reduction in the risk of neonatal death. Staying in SSC for more than 146.9 min/day seems to be clinically beneficial for these neonates mostly when it was associated with the absence of infection.